Performance Analysis and Characterization Hybrid Two Wheeller Vehicle with Using a Chassis Dynamometer - Julian Fikri Arifwardana; Dominicus Danardono Dwi Prija Tjahjana; Muhammad Nizam; Ihsan Pratama Rushadiawan; Mufti Reza Aulia Putra (Universitas Sebelas Maret (UNS), 2024)
The extraordinary growth in means of transportation, especially vehicles with internal combustion engines, has made state laws and regulations increasingly stringent. Regulations regarding energy consumption used for passenger and personal mobility and the emissions produced in order to reduce pollution. A hybrid vehicle combines two energies produced from various sources such as an ICE and an electric motor to become a hybrid electric vehicle (HEV). This research discusses hybrid electric vehicles on 2-wheeled vehicles which can be used as a solution that can be developed further before pure electric vehicles (EV) replace motorized vehicles (ICE). This research was done experimentally, by carrying out tests on a dynamometer and on the road testing. The main material used in this research was a Honda PCX 150 vehicle. The results of the test on the dynamometer showed that the performance of the internal combustion engine (ICE) had a torque of 11.12 Nm and a power of 8.20 kW at 7000 rpm. Testing the electric motor (EV), obtained torque results of 11.7 Nm and 2.33 kW power. The road test results for internal combustion engine consumption to consume 1 liter of fuel, capable of covering a distance of 54.55 km. Electricity consumption from 100% to 0% SOC can cover a distance of 46.31 km. Hybrid consumption 1 liter of fuel and battery full 100% capable of covering a distance 57.79 km, with battery condition reduced 16%.